xy"+2y'=0 reduced into y
Given xy"+2y'=0
let z=y′. ---------------------------------(i)
Then, dz/dx=y".
Given equation reduces to,
x(dz/dx)=−2z, ( by using separable variables )
=>−dz/z=2dx/x.
Integrating both sides, we get
=>-logz =2logx+Log(c),where c is an arbitrary constant.
=>-logz =log(cx^2)
=> z=Cx^(-2), where C is an arbitrary constant.
Now, from equation (i).
We get,
=>dy/dx=C x^(-2)
Integrate above , we get
=>y=-C(1/x)+c1
Comments
Thank you so much for solving assignmentexpert
Leave a comment